The inequality of 生词 meaning in comprehensive Chinese books on Indonesian learners: A translation analysis study - Dewi, Endah Putri; Adhimas , Yogi Bagus (Universitas Negeri Malang, 2023)
This study aims to determine the inequality of Chinese translation into English and Indonesian, because differences in meaning will affect the meaning of each word translated into different languages, this difference has a very dangerous effect if there is an error in translation, one language and the other have their own characteristics and language styles, and have rules and are bound by their respective cultures and nationalities, To minimize errors or errors in translation, it is necessary to pay close attention to the word when in a sentence it will have a different meaning when combined with other sentences.